The Associated Factors with Breastfeeding Self-Efficacy Among Breastfeeding Women in Kalimantan Utara - Widiya Rolantika; Annisa Nurrachmawati; Ike Anggraeni (EMBRIO: Jurnal Kebidanan, 2024)
Exclusive breastfeeding is important for the quality of children's health. Nevertheless, the proportion of exclusive breastfeeding at the Malinau City Health Center stands at a mere 45.6 percent, falling short of the 50 percent benchmark set by the World Health Organization (WHO). nursing self-efficacy is a significant element that affects nursing behavior. This study aims to determine the factors related to breastfeeding self-efficacy. This study was cross-sectional, with a sample of 147 mothers obtained by purposive sampling. Breastfeeding Self Efficacy (BSE) is measured using the Breastfeeding Self Efficacy Short-Form. Data was analyzed using the Chi-Square test. The results showed that there was a significant relationship between breastfeeding problems (p-value equals 0.001), family support (p-value equals 0.001), and health worker support (p-value equals 0.001) with breastfeeding self-efficacy. It is concluded that breastfeeding problems, family support, and health worker support were factors related to breastfeeding self-efficacy in breastfeeding mothers. Therefore, health workers and families are expected to support mothers when they have breastfeeding problems